PENTINGNYA KARAKTERISTIK TUNGKU UNTUK MENCIPTAKAN BEBAN, HARGA JUAL, DAN PROFITABILITAS PATUNG BARONG BERMEDIA KERAMIK - Normal, I Nyoman (Jurnal Keuangan dan Perbankan, 2015)
The aim of this research was to determine the influence of stove characteristics to production cost price, saleprice, and profitability. The research results showed that the stove characteristics influenced the productioncost price of barong statue. The production cost price of barong statue by small stove was Rp 93.495,95 eachunit, by medium stove was Rp 91.423,81 each unit, and by big stove was Rp 89.040,23 each unit. The costprice of production of barong statue decreased 2,21 % for medium stove, and 4,76% for big stove. From thefinancial management side, the good management of financial resources in manufacturing barong statue couldcreate more accurate the production cost price; the stove characteristics influenced cost price of barong statue.The sale price of barong statue by small size stove was Rp 121.539,54 each unit, by medium stove was Rp118.850,95 each unit, and by the big stove was Rp 115.752,30 each unit. The sale price of barong statuedecreased 2,21% for medium stove, and 4,76% for big stove. The determination of cost price exactly couldcreate financial structure well because cost price is an element of sales; and the stove characteristics influencedthe profitability of barong statue. The profitability of barong statue by small stove was 11,54%, by mediumstove was 11,54%, and by big stove was 11,54%. The profitability of barong statue did not differ from thesmall, medium and big stove. The management of fire stove and productive assets effectively could increaseprofitability as part of financial management for short term, middle term, and long term.